2022
DOI: 10.4038/cjs.v51i2.8008
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of two types of microplastics on <em>Solanum lycopersicum</em> L. and arbuscular mycorrhizal fungi

Abstract: Microplastics (MPs) in agricultural soils are a major concern. Relatively few studies have been carried out to explore its potential impacts on crops and soil microbiota. The study investigates the effects of two different types of MPs (microfiber, MFB and microfilms, and MFL) on the growth of Solanum lycopersicum L. (tomato) and Arbuscular Mycorrhizal Fungi (AMF). A pot experiment was conducted with MFB and MFL concentrations viz., 0.4, 2.4, 4.4, 6.4, and 8.4% (w/w) and control without MPs (n = 6). Plant he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Reduced germination of wheat seeds, hindered root development, and changes in the microbial composition of soil after exposure to microplastics, which could endanger soil ecosystems and wheat yield [6]. Furthermore [7] observed that the presence of microplastics in tomato environments resulted in altered fruit traits, reduced fruit yield, and disruptions in soil microbial communities. These findings raise concerns for the health of the soil and tomato production in areas where microplastics are present.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced germination of wheat seeds, hindered root development, and changes in the microbial composition of soil after exposure to microplastics, which could endanger soil ecosystems and wheat yield [6]. Furthermore [7] observed that the presence of microplastics in tomato environments resulted in altered fruit traits, reduced fruit yield, and disruptions in soil microbial communities. These findings raise concerns for the health of the soil and tomato production in areas where microplastics are present.…”
Section: Introductionmentioning
confidence: 99%